(untitled) (Entrepreneurship Journal for Finance and Business, 2020)
The research aims to shed light on the effect of credit risk on the share prices that economic units are exposed to, represented by commercial banks, the sample of the research, as a result of the credit facilities they grant, which are represented in loans and advances, and since these units earn profits through credit facilities, they bear some risks due to some default In terms of payment, where the risks relate to the return directly, as the higher the return, the greater the risk. As for the research sample, it was represented by commercial banks, which amounted to five banks listed on the Iraq Stock Exchange for the period from (2015-2019). Financial indicators were used to measure these risks as well as the use of the SPSS program. To analyze the data and test hypotheses, a set of conclusions and recommendations were reached that support the research, and the results showed a statistically significant effect of non-performing loans on stock prices. The research also found a statistically significant effect of the provision for credit losses on stock prices. Bad loans for some banks reached a dangerous stage, reaching (1.09) for the Assyrian Bank for the year (2017) and the Bank of Baghdad (0.82) for General (2018).